2020
DOI: 10.3390/jcm9061954
|View full text |Cite
|
Sign up to set email alerts
|

Dominantly Inherited Hereditary Nonpolyposis Colorectal Cancer Not Caused by MMR Genes

Abstract: In the past two decades, multiple studies have been undertaken to elucidate the genetic cause of the predisposition to mismatch repair (MMR)-proficient nonpolyposis colorectal cancer (CRC). Here, we present the proposed candidate genes according to their involvement in specific pathways considered relevant in hereditary CRC and/or colorectal carcinogenesis. To date, only pathogenic variants in RPS20 may be convincedly linked to hereditary CRC. Nevertheless, accumulated evidence supports the involvement in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 125 publications
1
12
0
2
Order By: Relevance
“…Thirdly, some patients probably have pathogenic variants in regions that our analysis was not designed to capture, such as deep intronic or regulatory variants in known cancer genes or variants in genes not yet identified or associated with CRC. Many genes have been suggested as candidate colorectal genes, and especially genes such as POLE2, MRE11, and POT1 appear to be interesting genes as well as epigenetic changes in PTPRJ (Venkatachalam et al, 2010;Chubb et al, 2016;Terradas et al, 2020). Another possibility is a non-mendelian predisposition to CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, some patients probably have pathogenic variants in regions that our analysis was not designed to capture, such as deep intronic or regulatory variants in known cancer genes or variants in genes not yet identified or associated with CRC. Many genes have been suggested as candidate colorectal genes, and especially genes such as POLE2, MRE11, and POT1 appear to be interesting genes as well as epigenetic changes in PTPRJ (Venkatachalam et al, 2010;Chubb et al, 2016;Terradas et al, 2020). Another possibility is a non-mendelian predisposition to CRC.…”
Section: Discussionmentioning
confidence: 99%
“…The rapid development of sequencing-based techniques and genome-wide copy number techniques brought hope for the identification of new causal genes for nonpolyposis familial and EOCRC. However, despite the enormous efforts made, which led to the identification of over a hundred candidate genes (reviewed by Terradas et al [ 35 ]), up to date only RPS20 has shown consistent association with hereditary nonpolyposis CRC. Among the other ≈100 candidate genes identified, nine currently show promising evidence to support their involvement in CRC predisposition: MRE11 , BARD1 , POT1 , BUB1B , POLE2 , BRF1 , IL12RB1, and PTPN12 , and the epigenetic alteration of PTPRJ [ 35 ].…”
Section: Inherited Syndromes That Predispose To Eocrcmentioning
confidence: 99%
“…However, despite the enormous efforts made, which led to the identification of over a hundred candidate genes (reviewed by Terradas et al [ 35 ]), up to date only RPS20 has shown consistent association with hereditary nonpolyposis CRC. Among the other ≈100 candidate genes identified, nine currently show promising evidence to support their involvement in CRC predisposition: MRE11 , BARD1 , POT1 , BUB1B , POLE2 , BRF1 , IL12RB1, and PTPN12 , and the epigenetic alteration of PTPRJ [ 35 ]. Additional candidate genes are published on a regular basis that require validation in large cohorts and functional studies that support their involvement in colorectal carcinogenesis.…”
Section: Inherited Syndromes That Predispose To Eocrcmentioning
confidence: 99%
See 1 more Smart Citation
“…Their clinical management is thus conducted based on their family history. Important efforts have been made to identify new high or moderate penetrance genes that explain the familial aggregation, early ages of onset, or polyposis phenotypes observed in those families or individuals, but the success achieved has been minimal [3][4][5].…”
Section: Introductionmentioning
confidence: 99%